Identifying the optimal safety leader: a person-centered approach. Issue 3 (8th March 2021) - Willis, Sara; Clarke, Sharon; O'Connor, Elinor
Abstract : Purpose: The research aimed to uncover leader profiles based on combinations of transformational (TFL), transactional (TAL) and passive leadership (PAL) and to examine how such constellations affect safety. Leader adaptability was tested as an antecedent of leader profiles. Design/methodology/approach: Using latent profile analysis, the effect of different leader profiles on workplace safety was investigated in two survey studies. Findings: In total, four leader profiles emerged: "active, " "stable-moderate, " "passive-avoidant" and "inconsistent" leader. A stable-moderate leader profile was identified as the optimal leader profile for safety performance. Leader adaptability was identified as a predictor of leader profile membership. Practical implications: Safety leadership development should focus on training managers in optimal combinations of leadership practices. Originality/value: The research calls into question the existence of a transformational or transactional leader. The findings suggest that higher frequency of leadership practices is not always more beneficial for workplace safety.